Теоретический анализ условий повышения точности обработки при развертывании отверстий - Брижан, Т. М.; Дитиненко, Станислав Александрович (Национальный технический университет "Харьковский политехнический институт", 2014)
В работе предложена математическая модель определения составляющих силы резания при развертывании отверстий с позиции косоугольного резания, что позволило обеспечить высокую сходимость расчетных и экспериментальных данных. Теоретически и экспериментально обоснована возможность существенного снижения тангенциальной и радиальной составляющих силы резания за счет создания наклонных зубьев на развертке, что способствует повышению точности обработки отверстий. Показано значительное влияние интенсивности трения на передней поверхности зуба развертки на силы резания при развертывании отверстия.

The paper presents a mathematical model for determining the components of the cutting forces when deployed holes with oblique cutting positions that will ensure a high convergence of calculated and experimental data. Theoretically and experimentally demonstrated the possibility of a significant reduction in the tangential and radial component of the cutting force due to the creation of inclined teeth on the scan, thereby increasing the accuracy of machining holes. In particular as it relates to the treatment of holes with uneven allowance when formed unbalanced radial component of the cutting force, which determines the error handling. Significant influence of the intensity of the friction on the front surface of the tooth to sweep the cutting forces when deployed holes. It is found that incorporating friction forces converging chip along the cutting tooth scan allows you to bring the calculated values of the tangential, radial and axial components of the cutting force to the experimental values. Practical recommendations for improving the accuracy of treatment in the deployment of holes.
Theoretical analysis of the conditions for improving the accuracy of treatment in the deployment of holes
Keywords: развертывание отверстий; зубья развертки; механическая обработка; точность обработки; сила резания; коэффициент усадки стружки; deployment of holes; teeth sweep; machining; precision machining; cutting force; shrinkage factor shavings